Arabic Panegyrics On The Prophet In Tamil Nadu State Of India Cultural Reverence - Zubair K M A, Ahamed; Ali, M.Yasar Arafath; Lebbai, Nahvi Muhiyadeen; Hameed, A. Ahamed Shahul; Naina, K. Seyad Ahmed (Ijaz Arabi Journal of Arabic Learning, 2024)
This research article explores the significance of panegyrics in Arabic on the Prophet in the Arabic literature of Tamil Nadu, India. Panegyrics, known as al-Madaih al-Nabawiyyah, are prominent in Islamic culture and express profound love, respect, and loyalty towards the Prophet. The article examines the historical background of panegyrics and their decline during the emergence of Islam. It discusses the poets who composed panegyrics in the presence of the Prophet and their alignment with the decline of pagan poetry. Additionally, the article highlights the relationship between panegyrics and Sira (biography), their formalization, and their association with Islamic mysticism. It focuses on notable panegyric compositions by scholars from Tamil Nadu, discussing their themes and contributions to Arabic literature. The article concludes by emphasizing the diversity of styles and meanings in prophetic panegyrics and their integration and cultural reverence into Sufism.